Determination of culture process for obtaining basidiocarp of pleurotus eryngii (DC. ex Fr.) Quel. var. ferulae Lanzi: A speciality mushroom - Akyüz, Mehmet; Kirbag, Sevda (Indian Academy of Horticultural Sciences, 2010)
The present study is to investigate the obtained basidiocarp and culture process of P. eryngii var. ferulae grown naturally in Elazi? region of Turkey. The pure mycelium cultures of P. eryngii var. ferulae was maintained on malt-extract agar. Wheat grain was used in the production of spawn. Wheat straw was used as substrate for the cultivation. The spawn growing period was 15 days, the first and second primordium formation period was 111 and 146 days, respectively. The first harvest period was 126 days, and the second was 161 days. In the first harvest; yield per 100 g of material (70% moisture) was 24.8 g and the second harvest yield was 7 g (g 100 g-1). Based on the results, P. eryngii var. ferulae was succesfully cultivated.
Keywords: Basidiocarp; Culture process; P. eryngii var. ferulae; Yield